Avaliação de perda de grãos na colheita mecânica de soja, na região do ’Pontal do Triângulo Mineiro’ - Martins, Oswaldir; Silva Reis, Múcio; Sediyama, Tuneo; Gonzaga Pereira, Messias; Sigueyuki Sediyama, Carlos (Revista Ceres, 2025)
During 1978 and 1979, 11 soybean fields in the «Pontal do Triângulo Mineiro» region, Minas Gerais, were surveyed to evaluate the different types of soybean losses and bean damage as caused by combine harvesting.